Rasionalitas Penggunaan Antibiotik terhadap Pengobatan Pneumonia di Rumah Sakit X Utara Tahun 2023 - Bella Surbakti, Rindi Maudhy May; Sahputri, Juwita; Yuziani, Yuziani (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Pneumonia is an acute inflammation of the lung parenchyma from an acute lower respiratory tract infection which can be caused by various infectious agents, namely bacteria, viruses, fungi and parasites. The treatment therapy that is generally used to treat pneumonia is rational administration of antibiotics. By assessing the rationality of antibiotic use, it can support effectiveness both in terms of cost, side effects or toxicity and of course prevent resistance to antibiotic use. The general aim of this research is to determine the rationality of the use of antibiotics for the treatment of pneumonia at X Hospital, North Aceh using the Gyssens method based on the Ministry of Health guidelines. This research is descriptive in nature. Samples were taken using purposive sampling technique. The research results showed that the patient was male, and the patient was elderly (> 60 years). This study found that ceftriaxone was the most frequently prescribed antibiotic, followed by ceftazidime, fosmicin and levofloxacin. For rationality, there is levofloxacin which is classified as category 0, namely antibiotics that are used appropriately and wisely, category III A for ceftriaxone and levofloxacin, namely the use of antibiotics is still inappropriate when the time of administration is too long, category III B for ceftriaxone, namely administration at too short a time interval, and category IV A for ceftriaxone, ceftazidime and fosmicin, which indicates that they are not more effective. The conclusion of this study is that pneumonia patients are male, aged > 60 years and in the elderly category, the most frequently used antibiotic is ceftriaxone, while many of the levels of rationality are still classified as irrational.